2010
DOI: 10.1161/circulationaha.109.869156
|View full text |Cite|
|
Sign up to set email alerts
|

Novel Associations of Multiple Genetic Loci With Plasma Levels of Factor VII, Factor VIII, and von Willebrand Factor

Abstract: Background Plasma levels of coagulation factors VII (FVII), VIII (FVIII), and von Willebrand factor (vWF) influence risk of hemorrhage and thrombosis. We conducted genome-wide association studies to identify new loci associated with plasma levels. Methods and Results Setting includes 5 community-based studies for discovery comprising 23,608 European-ancestry participants: ARIC, CHS, B58C, FHS, and RS. All had genome-wide single nucleotide polymorphism (SNP) scans and at least 1 phenotype measured: FVII activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
356
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 328 publications
(392 citation statements)
references
References 65 publications
(51 reference statements)
31
356
5
Order By: Relevance
“…Interestingly, according to the HapMap database, the rs10133762-G allele found to be associated with increased VWF levels [1] corresponds to the rs1884841-T allele associated with increased risk of VT, this observation being consistent with the well-known association between VWF levels and VT risk. It is worth noting that the rs10133762-G allele was associated with increased VWF plasma levels but no association was reported with FVIII [1]. In the TC2N gene where these two SNPs map has three different isoforms, one of them has an additional exon in its 5¢ sequence.…”
supporting
confidence: 74%
See 2 more Smart Citations
“…Interestingly, according to the HapMap database, the rs10133762-G allele found to be associated with increased VWF levels [1] corresponds to the rs1884841-T allele associated with increased risk of VT, this observation being consistent with the well-known association between VWF levels and VT risk. It is worth noting that the rs10133762-G allele was associated with increased VWF plasma levels but no association was reported with FVIII [1]. In the TC2N gene where these two SNPs map has three different isoforms, one of them has an additional exon in its 5¢ sequence.…”
supporting
confidence: 74%
“…This SNP was studied because it is in nearly complete association with the rs10133762 found modulating plasma levels of VWF in the CHARGE consortium [1]. Interestingly, according to the HapMap database, the rs10133762-G allele found to be associated with increased VWF levels [1] corresponds to the rs1884841-T allele associated with increased risk of VT, this observation being consistent with the well-known association between VWF levels and VT risk. It is worth noting that the rs10133762-G allele was associated with increased VWF plasma levels but no association was reported with FVIII [1].…”
supporting
confidence: 55%
See 1 more Smart Citation
“…Although we do not discuss the results in this review, GWAS for coagulation and fibrinolysis have also been reported. [81][82][83][84][85] Associations at 12q24 Given the close biological relationship between PLT and CAD, 3 Soranzo et al 28 evaluated the risks of CAD in the loci associated with PLT and found an overlap between these two traits at 12q24. The variants identified at 12q24 were encompassed by a long-range haplotype that extended 41.5 Mbps on which significant pressure of natural selection was observed.…”
Section: Genetic Factors For Pltmentioning
confidence: 99%
“…Chosen based on data from Atherosclerosis Risk in Communities (ARIC) study (European ancestry) (Campos et al 2011, Smith et al 2010 and data on expression in cardiovascular disease (van Schie et al 2011). …”
Section: Polymorphisms Of Interestmentioning
confidence: 99%